Group Guidance Based on The Javanese Philosophy of Life Memayu Hayuning Bawana to Improve Pro-Social Behavior of Adolescents (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
Humans and culture are interconnected entities, so the practitioner's culture must also guide guidance and counseling practices. Current guidance and counseling practices in Indonesia are still centered on Western culture, even though Indonesia has many cultural values that can be integrated into guidance practices. Memayu Hayuning Bawana is a Javanese (Indonesian) philosophy of life, meaning to make the world beautiful. In a situation of increasing antisocial behavior among adolescents, the philosophy of life of Memayu Hayuning Bawana is relevant to be accommodated in the lives of adolescents to increase pro-social behavior. Previous research has shown that group guidance effectively increases pro-social behavior in adolescents, especially in Indonesia. This literature study aims to analyze the values contained in Memayu Hayuning Bawana's philosophy of life and create a prototype model of group guidance based on Memayu Hayuning Bawana to increase pro-social behavior in adolescents. This literature review aims to complement the existing literature on group guidance interventions to increase pro-social behavior. The novelty of this study lies in integrating the concept of Memayu Hayuning Bawana into psychological interventions. This research falls within the scope of indigenous counseling because it incorporates local cultural values as the basis for intervention. The literature review indicates that group counseling based on the Javanese philosophy of life, "Memayu Hayuning Bawana," effectively improves prosocial behavior among Indonesian adolescents